Republic of Poland : Financial Sector Assessment Program-Technical Note-Macroprudential Policy Framework. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This Technical Note on Macroprudential Policy Framework for the Republic of Poland highlights that the present macroprudential policy framework provides a sound basis for macroprudential oversight of the financial system and was established by law in November 2015. Its relatively recent establishment implies that practical experience with the conduct of macroprudential policy under the framework is still limited. Initial experience is favorable, however, it remains to be seen how the framework will function under more challenging circumstances. The Financial Stability Committee-Macroprudential (FSC-M) has recommended a variety of measures to provide incentives for voluntary restructuring of foreign exchange housing loans extended by Polish banks. It is recommended that the FSC-M further strengthens its communication in order to increase transparency and accountability, considers a more active use of targeted statements as a policy instrument, and increases the involvement of external experts in the preparation of its meetings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet